2019
DOI: 10.1007/s40200-019-00445-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of melatonin in restoring the antioxidant status in the lens of diabetic rats induced by streptozotocin

Abstract: Background Melatonin is a well-known free radical scavenger. The present study aimed to investigate the effects of melatonin treatment on the antioxidant status in the lenticular tissue of streptozotocin (STZ)-induced diabetic rats. Methods Thirty-four male rats were randomly divided into four groups as follows: healthy control rats (group 1, n = 10); diabetic control rats (group 2, n = 10); melatonin-treated (5 mg/kg•day) diabetic rats (group 3, n = 10) and melatonin-treated (5 mg/kg• day) healthy rats (group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
(51 reference statements)
1
5
0
Order By: Relevance
“…After the first week, the blood glucose levels of the rats that were treated with insulin, melatonin, or a combination of the two agents seemed to return to those of the controls. Interestingly, melatonin was found to regulate the blood glucose levels in a manner similar to that observed for insulin therapy in earlier studies (Andersson & Sandler, 2001; Khorsand, Akmali, & Akhzari, 2019; Montilla et al., 1998). The increase in the MDA and 8‐OHdG levels and caspase‐3 activity, in addition to the concomitant decrease in the cGMP levels and NOS activity, suggested the presence of hyperglycemia‐induced oxidative stress on the CC.…”
Section: Discussionsupporting
confidence: 68%
“…After the first week, the blood glucose levels of the rats that were treated with insulin, melatonin, or a combination of the two agents seemed to return to those of the controls. Interestingly, melatonin was found to regulate the blood glucose levels in a manner similar to that observed for insulin therapy in earlier studies (Andersson & Sandler, 2001; Khorsand, Akmali, & Akhzari, 2019; Montilla et al., 1998). The increase in the MDA and 8‐OHdG levels and caspase‐3 activity, in addition to the concomitant decrease in the cGMP levels and NOS activity, suggested the presence of hyperglycemia‐induced oxidative stress on the CC.…”
Section: Discussionsupporting
confidence: 68%
“…Some studies reported that melatonin improves insulin sensitivity, increases insulin secretion and prevents hyperglycemia. [43][44][45] However, others showed that melatonin treatment does not significantly affect the blood glucose in diabetic animals, but can still alleviate diabetic cardiac dysfunction through preventing mitochondrial fission, reducing myocardial oxidative stress, inducing cardiac autophagy and limiting myocardial apoptosis. 19,20,36,38,46 Moreover, the recently published results from highly cited prospective randomized clinical trials failed to demonstrate improvement of cardiovascular prognosis with aggressive glycemic control.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this issue has been controversial. Some studies reported that melatonin improves insulin sensitivity, increases insulin secretion and prevents hyperglycemia . However, others showed that melatonin treatment does not significantly affect the blood glucose in diabetic animals, but can still alleviate diabetic cardiac dysfunction through preventing mitochondrial fission, reducing myocardial oxidative stress, inducing cardiac autophagy and limiting myocardial apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…A marker of oxidative stress, serum GSH, was reported to be lowered by streptozotocin treatment [12] . The MDA in the untreated streptozotocin rat increased dramatically [13] , and the GSH activity significantly decreased in comparison to the control groups [14] . Improvement in pancreatic structure was evident in group V, possibly as a result of vitamin E's antioxidant properties, which reduce oxidative stress and shield pancreatic cells from the creation of free radicals while promoting cellular regeneration and proliferation [15] .…”
Section: Discussionmentioning
confidence: 81%